Child Cortisol Output During Cold Pressor Task is Associated with Trait Anxiety, but Not Maternal Antenatal Depression. (September 2021) - Sawyer, K.M.; Bind, R.H.; Hazelgrove, K.; Allegri, B.; Rebecchini, L.; Osborne, S.; Conroy, S.; Sethna, V.; Pariante, C.M.
Abstract : Background: Antenatal depression is associated with heightened infant stress reactivity, but how long-lasting these changes are, what factors might protect against them, and what the impact is on psychiatric risk is unknown. Methods: The Psychiatry Research and Motherhood-Depression study recruited antenatally depressed women, and controls, who are now being followed at child age 7-9 years. Children completed the Depression Self-Rating Scale and the State-Trait Anxiety Inventory. Salivary cortisol output was calculated as AUC from before, to 40 minutes after, the Cold Pressor Task. Results: Children born of antenatally depressed and control mothers did not differ on their self-reported depression (z=0.32, p=0.75), state (z=-1.10, p=0.27) or trait anxiety (z=1.19, p=0.24), or cortisol output (t(39)=-1.82, p=0.076). Cortisol output was significantly correlated with child trait anxiety (r=0.34, p=0.030). Conclusion: These data indicate that, in this cohort, antenatal depression was not associated with child outcomes at 7-9 years. Instead, child cortisol output was associated with concurrent trait anxiety. This may suggest either that age 7-9 is too early, or, more encouragingly, that protective factors are present in this cohort which break the mother-child transmission cycle.